Media publiczne w Polsce a popularyzacja wiedzy o języku polskim - Grzelka, Monika; Kula, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2012)
One of the statutory provisions of public media is to popularize the knowledge of the Polish language – the present authors analyse diversified aspects determining the effectiveness of the execution of the task and the media’s commitment to its social responsibility, and proceed to evaluate the basic assignments and responsibilities involved in the journalistic profession. These responsibilities result largely from the reception of the profession by the general public, and from those that emerge within the context of studies on language authority figures in present-day Poland. The next stage of the analysis involves an evaluation of the activities of all-Polish national broadcasters in view of their practical implementation and execution of the commitments set in Art. 21, Section 1a, item 8 of the Radio and Television Act (diffusion and divulgation of the knowledge of the Polish language). The remaining part of the article, including postulative claims, results from an analysis of the activities popularizing the knowledge on Polish available in the media and from the conviction of the necessity of expanding them beyond just grammaticality and correctness in the language use.